(untitled) (Islas, 2024)
Introduction: The article delves into the main declarations and measures adopted by the Revolutionary Government concerning small private businesses. It systematizes the key events related to these businesses during the first decade of the Revolution. Methods: The research utilizes the analysis of historical and legal documents, such as speeches, periodical publications of the time, and current legal norms on the subject under study. Results: The article presents the essential elements of the relationship between the emerging Cuban Revolution and small private businesses, as well as the events related to these businesses until their disappearance from the national reality. Conclusions: In the early years of the Revolution, guarantees were offered to the owners of small private businesses, which were gradually eliminated due to the stance taken by these owners and the definition of the socialist character of the Cuban Revolution.